Orbital Interaction and Electron Density Transfer in PdII([9]aneB2A)L2 Complexes: Theoretical Approaches - Keum Kwak, Ock; Arooj, Mahreen; Yoon, Yong-Jin; Duck Jeong, Euh; Keun Park, Jong (M D P I AG, 2013)
The geometric structures of Pd-complexes {Pd([9]aneB2A)L2 and Pd([9]aneBAB)L2 where A = P, S; B = N; L = PH3, P(CH3)3, Cl−}, their selective orbital interaction towards equatorial or axial (soft A…Pd) coordination of macrocyclic [9]aneB2A tridentate to PdL2, and electron density transfer from the electron-rich trans L-ligand to the low-lying unfilled a1g(5s)-orbital of PdL2 were investigated using B3P86/lanl2DZ for Pd and 6-311+G** for other atoms. The pentacoordinate endo-[Pd([9]aneB2A)(L-donor)2]2+ complex with an axial (soft A--Pd) quasi-bond was optimized for stability. The fifth (soft A--Pd) quasi-bond between the σ-donor of soft A and the partially unfilled a1g(5s)-orbital of PdL2 was formed. The pentacoordinate endo-Pd([9]aneB2A)(L-donor)2]2+ complex has been found to be more stable than the corresponding tetracoordinate endo-Pd complexes. Except for the endo-Pd pentacoordinates, the tetracoordinate Pd([9]aneBAB)L2 complex with one equatorial (soft A-Pd) bond is found to be more stable than the Pd([9]aneB2A)L2 isomer without the equatorial (A-Pd) bond. In particular, the geometric configuration of endo-[Pd([9]anePNP)(L-donor)2]2+ could not be optimized.